Great phenotypic and genetic variation among successive chronic Pseudomonas aeruginosa from a cystic fibrosis patient - Lozano, Carmen (PLoS One, 2018)
BACKGROUND/OBJECTIVES: Different adapted Pseudomonas aeruginosa morphotypes are found during chronic infections. Relevant biological determinants in P. aeruginosa successively isolated from a cystic fibrosis (CF) patient were analyzed in this work to gain insight into P. aeruginosa heterogeneity during chronic infection. METHODS: Seventeen P. aeruginosa isolates collected from a patient over a 3 year period were included, 5 small colony variants (SCV) and 12 mucoids. The following analyses were performed: Pulsed-Field-Gel-Electrophoresis (PFGE)/Multilocus- sequence-typing (MLST)/serotype, antimicrobial susceptibility, growth curves, capacity to form biofilm, pigment production, elastase activity, motility; presence/expression of virulence/quorum sensing genes, and identification of resistance mechanisms. RESULTS: All isolates had closely related PFGE patterns and belonged to ST412. Important phenotypic and genotypic differences were found. SCVs were more resistant to antimicrobials than mucoid isolates. AmpC hyperproduction and efflux pump activity were detected. Seven isolates contained two integrons and nine isolates only one integron. All SCVs showed the same OprD profile, while three different profiles were identified among mucoids. No amino acid changes were found in MutL and MutS. All isolates were slow-growing, generally produced high biofilm, had reduced their toxin expression and their quorum sensing, and showed low motility. Nevertheless, statistically significant differences were found among SCV and mucoid isolates. SCVs grew faster, presented higher biofilm formation and flicA expression; but produced less pyorubin and pyocyanin, showed lower elastase activity and rhlR, algD, and lasB expression than mucoid isolates. CONCLUSION: These results help to understand the molecular behavior of chronic P. aeruginosa isolates in CF patients.